2010
DOI: 10.1007/s12080-010-0092-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional trade-offs fail to explain richness and structure in species-rich plant communities

Abstract: Mathematical models and ecological theory suggest that low-dimensional life history trade-offs (i.e. negative correlation between two life history traits such as competition vs. colonisation) may potentially explain the maintenance of species diversity and community structure. In the absence of trade-offs, we would expect communities to be dominated by 'super-types' characterised by mainly positive trait expressions. However, it has proven difficult to find strong empirical evidence for such trade-offs in spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
(110 reference statements)
0
12
0
Order By: Relevance
“…Further, the two traits have coevolved, as revealed by the Bayesian MCMC analysis. Given that both more and larger seeds may be adaptive among nonsprouters, as they regenerate solely from seeds after fire and their seedlings establish in nutrient-impoverished environments [ 27 , 24 ], this fire-response type opts for more rather than larger seeds. Extensive demographic studies on hakeas and related woody species in SWA have shown that postfire recruitment patterns conform to biased lotteries, with the demographic component paramount followed by biotic components, such as seedling size [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the two traits have coevolved, as revealed by the Bayesian MCMC analysis. Given that both more and larger seeds may be adaptive among nonsprouters, as they regenerate solely from seeds after fire and their seedlings establish in nutrient-impoverished environments [ 27 , 24 ], this fire-response type opts for more rather than larger seeds. Extensive demographic studies on hakeas and related woody species in SWA have shown that postfire recruitment patterns conform to biased lotteries, with the demographic component paramount followed by biotic components, such as seedling size [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…H 1 : Nonsprouters produce more seeds or larger seeds than resprouters [ 24 ], and have greater investment in seeds [ 13 , 25 , 30 , 29 ];…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various trait‐based simulation models of Mediterranean‐type ecosystems exist and have been used, for example, to assess the impact of climate and fire on vegetation composition or performance, none of these models can currently fully assist restoration efforts toward multifunctional and resilient ecosystems. For example, several model approaches neglect soil water and nutrient dynamics, as well as their feedbacks to vegetation dynamics (e.g., Esther et al., ; Moore & Noble, ; Pausas, ) and are therefore too simplified to assess the impact of global change. Other models explicitly consider water dynamics, but neglect nitrogen dynamics (e.g., Fyllas & Troumbis, ; Mouillot, Rambal, & Lavorel, ) and thus cannot account for the effects of nutrient deposition, for example, on invasive species or on ecosystem functions such as dissolved and particulate leaching and gaseous nutrient loss.…”
Section: Case Study—the Ridgefield Restoration Experimentsmentioning
confidence: 99%
“…For example, several model approaches neglect soil water and nutrient dynamics, as well as their feedbacks to vegetation dynamics (e.g., Esther et al, 2011;Moore & Noble, 1990;Pausas, 1999) and are therefore too simplified to assess the impact of global change.…”
Section: Step 1: Development Of Trait-based Simulation Modelmentioning
confidence: 99%